3D-Printed Poly-Caprolactone Scaffolds Modified With Biomimetic Extracellular Matrices for Tarsal Plate Tissue Engineering - Chen, Liangbo; Yan, Dan; Wu, Nianxuan; Zhang, Weijie; Yan, Chenxi; Yao, Qinke; Zouboulis, Christos C.; Sun, Hao; Fu, Yao (Frontiers in Bioengineering and Biotechnology, 2020)
Tarsal plate regeneration has always been a challenge in the treatment of eyelid defects. The commonly used clinical treatments such as hard palate mucosa grafts cannot achieve satisfactory repair effects. Tissue engineering has been considered as a promising technology. However, tarsal plate tissue engineering is difficult to achieve due to its complex structure and lipid secretion function. Three-dimensional (3D) printing technology has played a revolutionary role in tissue engineering because it can fabricate complex scaffolds through computer aided design (CAD). In this study, it was novel in applying 3D printing technology to the fabrication of tarsal plate scaffolds using poly-caprolactone (PCL). The decellularized matrix of adipose-derived mesenchymal stromal cells (DMA) was coated on the surface of the scaffold, and its biofunction was further studied. Immortalized human SZ95 sebocytes were seeded on the scaffolds so that neutral lipids were secreted for replacing meibocytes. In vitro experiments revealed excellent biocompatibility of DMA-PCL scaffolds with sebocytes. In vivo experiments revealed excellent sebocytes proliferation on the DMA–PCL scaffolds. Meanwhile, sebocytes seeded on the scaffolds secreted abundant neutral lipid in vitro and in vivo. In conclusion, a 3D-printed PCL scaffold modified with DMA was found to be a promising substitute for tarsal plate tissue engineering.